Studi Sosial Ekonomi Usaha Tani Padi (Studi Empiris Usaha Tani Padi Desa Kedung Banteng, Kecamatan Kedung Banteng, Kabupaten Tegal) - Oke Setiarso; Sukiman Sukiman (EKO-REGIONAL, 2012)
The purpose of this study is to know the characteristic rice farming in The Village Kedung Banteng and analyze the economic efficiency and technical efficiency in rice farming in the Village Kedung Banteng.Total population of rice farmers in the village Kedung Banteng  totaling 1825 people and taken 95 samples in . This research was conducted with qualitative and quantitative analysis based on production function with a stochastic frontier approach (Stochastic Frontier Production Function) included: regression analysis, maximum likelihood (MLE), the analysis of technical efficiency(DEA), economic efficiency and  price efficiency.The results show the estimation of stochastic frontier production function rice farming both in The Village Kedung Banteng there are only four significant independent variables namely labor, land , seed and capital. When viewed from the coefficient of elasticity, these inputs is elastic and when viewed from its RTS, rice farming in a state of increasing returns to scale (IRS), which the IRS values of 1,8747 in The Village Kedung Banteng. Based on analysis of technical efficiency (ET), it is known there are only 21 farmers who are efficient in  the Village Kedung Banteng at 100% efficiency rate. When viewed from the efficiency of the price / allocative and economic efficiency, the farming of rise has not been efficient with the efficiency of its value pricing 2,163 &1,758 in The Village Kedung Banteng economic efficiency  . From the calculation of technical efficiency, price efficiency, and economic efficiency can be concluded that rice farming has not been efficient. Value R/C ratio is 1.34 means rice farming profitable. Keywords: stochastic frontier, technical efficiency, economic efficiency, efficiency price.